Pemberdayaan Kampung Wisata Kuliner Pring Koening Bunulrejo Sebagai Wujud Kampung Tematik Khas Kota Malang - Rofieq, Mochammad; Siswati, Aris; Fauzy, Muchammad Riza (STIE Malangkucecwara, 2024)
One of the areas in Malang City where most of the residents are young people who are entrepreneurs in the culinary sector is in RT.02/RW.13, Bunulrejo Village, Blimbing District. The culinary MSME actors in this area formed a forum for joint activities called